2007
DOI: 10.1080/10428190701618268
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab, gemcitabine and oxaliplatin: An effective regimen in patients with refractory and relapsing mantle cell lymphoma

Abstract: Mantle cell lymphoma constitutes one of the lymphomas with poorest prognosis at relapse with limited effective salvage regimens due to advanced age. We present results of a new salvage regimen, rituximab, gemcitabine and oxaliplatin (GEMOX-R), in 14 patients with relapsing (n = 9) or refractory (n = 5) mantle cell lymphoma. The median number of cycles was 5.5 for a total of 72 cycles evaluated in the current study. The median age was 69.5 years with high-risk features. Patients received a mean number of prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Similar efficacy with GDP was observed by this group in HL with overall responses occurring in 70% of patients16. Though this trial was designed at a time when there was little published data on the efficacy of oxaliplatin in lymphoma, others have since evaluated the combination of gemcitabine and oxaliplatin, also demonstrating clinical activity in MCL and DLBCL 20,34. Our data contribute to this overall literature as the first multi-center prospective study to evaluate the safety and efficacy of a gemcitabine-carboplatin combination across a variety of relapsed lymphoid histologies.…”
Section: Discussionsupporting
confidence: 55%
“…Similar efficacy with GDP was observed by this group in HL with overall responses occurring in 70% of patients16. Though this trial was designed at a time when there was little published data on the efficacy of oxaliplatin in lymphoma, others have since evaluated the combination of gemcitabine and oxaliplatin, also demonstrating clinical activity in MCL and DLBCL 20,34. Our data contribute to this overall literature as the first multi-center prospective study to evaluate the safety and efficacy of a gemcitabine-carboplatin combination across a variety of relapsed lymphoid histologies.…”
Section: Discussionsupporting
confidence: 55%
“…There are few large studies evaluating the role of salvage chemotherapy programs in relapsed/refractory MCL. Generally, short median progression-free survival (PFS) of 5 to 12 months has been associated with salvage regimens including rituximab-fludarabinecyclophosphamide-mitoxantrone (R-FCM), rituximab-gemcitabineoxaliplatin (R-GemOx) and rituximab-dexamethasone-cytarabinecisplatin (R-DHAP) [33][34][35]. The largest of these studies examined the efficacy of R-FCM with or without rituximab maintenance in patients with relapsed/refractory mantle cell lymphoma.…”
Section: R-fcm R-gemox and R-dhapmentioning
confidence: 99%
“…As mentioned, established drugs such as nucleoside analogs have activity in MCL. Rodriguez et al [ 38 ] reported on GEMOX-R, a new salvage regimen in which 375 mg/m 2 of rituximab, 1000 mg/m 2 of gemcitabine, and 100 mg/m 2 of oxaliplatin were all given on day 1 every 2 to 3 weeks (most patients could not tolerate a 14-day schedule). Sixty-four percent of patients achieved CR (total response rate, 85%).…”
Section: Relapsed Diseasementioning
confidence: 98%